Socio-demographic characteristics and students’ entrepreneurial intentions - Ana Jovičić Vuković; Ivana Jošanov-Vrgović; Slobodanka Jovin; Nataša Papić-Blagojević (Stanovništvo)
This paper aims to analyse the entrepreneurial intentions of tourism students, who represent a significant base of future entrepreneurs and are the drivers of innovations and competitiveness in the travel and tourism industry, which is an important part of the economy of the Republic of Serbia. The study examined whether there are differences in students’ entrepreneurial intentions depending on socio-demographic characteristics: gender, place of residence, years of study, and previous work experience, as well as their parents’ education and type of employment. The survey was conducted in four higher vocational schools in Serbia on a sample of 330 students of tourism and hospitality management using the Entrepreneurial Intention Scale. The results showed that students had medium intention to start and run their own business and indicate that – among the selected socio-demographic factors – gender, years of study, and prior work experience play an important role in fostering entrepreneurial intentions. Understanding the factors that impact entre-preneurship may contribute to the development of theory in this field, as well as helping paint a clearer picture of how entrepreneurial intentions are formed as a starting point in business.